A randomized-controlled trial focusing on socio-economic status for promoting vegetable intake among adults using a web-based nutrition intervention programme: study protocol - Nakamura, Saki (BMC Public Health, 2017)
BACKGROUND: Web-based nutritional education programmes appear to be comparable to those delivered face-to-face. However, no existing web-based nutrition education or similar programme has yet been evaluated with consideration of socio-economic status. The objective of a nutritional education programme of promoting vegetable intake designed a randomized controlled trial (RCT) is to evaluate the results of intervention and to determine how socio-economic status influences the programme effects. METHODS/DESIGN: Participants will be randomly sampled individuals (aged 30–59) stratified according national population statistics for sex, age, and household income. Participants were consented to survey participation (n = 1500), and will be randomly divided into intervention and control groups. The intervention period is 5 weeks with one step of diet-related education per week. The main outcome of the programme is dietary behaviour as eating vegetable (350 g per day, five small bowl). To encourage behavioural changes, the programme contents are prepared using behavioural theories and techniques tailored to the assumed group stages of behavioural change. In the first step, we employ the health belief model to encourage a shift from the pre-contemplative to the contemplative phase; in the second and third steps, social cognitive theory is used to encourage transition to the preparatory phase; in the fourth step, social cognitive theory and strengthening social support are used to promote progression to the execution phase; finally, in the fifth step, strengthening social capital and social support are used to promote the shift to the maintenance phase. The baseline, post intervention and follow-up survey was assessed using a self-administered questionnaire. For process evaluation, we use five items relating to programme participation and satisfaction. A follow-up survey of participants will be carried out 3 months after intervention completion. DISCUSSION: The fact that this study is an RCT with an established control group is a strong advantage. Information and communications technology is not limited by time or place. If we could show this web-based nutrition education programmes has a positive effect, it may be an appropriate tool for reaching individuals in lower socio-economic state. TRIAL REGISTRATION: Current Controlled Trials UMIN-ICDR UMIN 000019376 (Registered October 16, 2015).